2016
DOI: 10.1039/c5ta10773c
|View full text |Cite
|
Sign up to set email alerts
|

An effective approach to improve the electrochemical performance of LiNi0.6Co0.2Mn0.2O2 cathode by an MOF-derived coating

Abstract: We report an effective surface modification for NCM-622, using MOF-derived alumina (MDA) coatings. The coated NCM-622 shows greatly enhanced performance: 214.6 and 196.5 mA h g−1 at 0.2C and 1C, respectively, with capacity retention of 92.7% after 100 cycles at 1C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…It is reported that Li-rich materials are composed of two phases of Li 2 MnO 3 (C 2/m ) and LiMO 2 (R m 3 ) (M = Ni, Co, Mn, etc.). [17][18][19] From this viewpoint, metal fluorides (FeF 3 , [20] MOF, [21,22] AlF 3 , [23,24] etc. [9][10][11][12][13] In this regard, multifarious modification approaches, such as doping and surface coating, have been intensively investigated.…”
mentioning
confidence: 99%
“…It is reported that Li-rich materials are composed of two phases of Li 2 MnO 3 (C 2/m ) and LiMO 2 (R m 3 ) (M = Ni, Co, Mn, etc.). [17][18][19] From this viewpoint, metal fluorides (FeF 3 , [20] MOF, [21,22] AlF 3 , [23,24] etc. [9][10][11][12][13] In this regard, multifarious modification approaches, such as doping and surface coating, have been intensively investigated.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] As research continues to combat voltage fade, interest in the lithium-stoichiometric, manganese-bearing, nickel-rich layered oxides (Li 1+x Ni a Co b Mn c O 2 , x typically <0.05) has been rekindled. [20][21][22][23][24][25][26] Oxides, such as LiNi 0. 5 In this article we focus our attention on the NCM523 oxide which has been the subject of several recent articles.…”
mentioning
confidence: 99%
“…At the same time, they also prepared Al 2 O 3 coated NCM622 and found that a layered structure of LiAlO 2 coating was formed, which decreased the contact area between the active material and electrolyte and reduced the interfacial resistance between the cathode and the electrolyte [34]. Li et al [35] reported an effective surface modification for NCM622 that an Al-based MOF (NH 2 -MIL-53) was used as a precursor to produce MOF-derived alumina (MDA) coatings. The MDA layer showed well-dispersion and the amorphous nature and could not block the pathways of Li + ions.…”
mentioning
confidence: 99%